STRENGTH PARAMETERS OF COLLEGE STUDENTS IN ISOKINETIC MODE IN FRONT CRAWL SWIMMING (Fiep Bulletin - online, 2014)
In this paper we evaluate the level of strength abilities in isokinetic mode male and female students of Faculty of Physical Education and Sport, Comenius University in Bratislava, specialization conditioning coach in front crawl swimming. Force parameters were investigated on a solid curtain of water at the specified speed swimming. The aim of the research was to determine the level of force parameters in front crawl swimming and set the optimal speed swimming at the trial for the college students. At swimming isokinetic dynamometer, we tested 13 students, swim at speeds of 0.3 ms-1 to 0.6 ms- 1. Filed of female students (n 10) were evaluated in swimming speed of 0.2 ms-1 to 0.5 ms-1. The results were registered in the computer software Fitronic Swim. We evaluated parameters of force and power. Motor test lasted 10 s. We registered changes of maximum and average force at specific swimming speed. In a group of students, we noted a gradual decline in maximum force of 141 N at a speed of swimming 0.3 ms-1 to 96.7 N in swimming speed 0.6 ms-1. The average force in the set had a similar trend with lower power (Fig.1) output parameter (the product of force and velocity) and the maximum average power was increasing the marginal rate of 0.4 ms-1 and at higher swimming speeds decreased (Fig.1). Based on the results we determine the optimal speed for the students to swim objective evaluation of force parameters 0.4 ms-1, and for female students 0.3 ms-1.
Keywords: university students; free style swimming; force; power; isokinetic mode